Las raíces de la violencia y el machismo: la socialización educativa a través de los videojuegos: (primera parte) (Papeles, 2009)
In this article, we question if certain violent climates taking place in classrooms won’t be caused by the society in which we live, and specifically, in this case, by the attitudes and behaviours reached by the more and more frequent use of videogames among the child and teenage population. Starting from the analysis of the contents and values which stimulate the publicity promoting them, and the research between the child and teenage students, we reach to the conclusion that these videogames, designed only to achieve economic profitability, are one of the explanatory keys which help to keep and boost aggressive relations, disdain and a violent climate hidden among the child and teenage population. Moreover these not only encourage them to adopt the consumer and predominant male values at a very early stage but also educate them against the social conventions, the ethics and the human rights.
Keywords: Videogames, school violence, school organization, stereotypes, sexism.